2011
DOI: 10.1111/j.1365-2885.2011.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enrofloxacin on cytochromes P4501A and P4503A in Carassius auratus gibelio (crucian carp)

Abstract: Currently, although enrofloxacin (EF) as a widely used veterinary medicine has begun to apply to treating fish bacterial infections, the researches on the effects of EF on their main drug metabolic enzymes are limited. To investigate the effects of EF on fish cytochromes P450 (CYPs) 1A and 3A, the enzymatic activities and expressions (mRNA and protein) of crucian carp CYP1A and CYP3A after EF administration were examined. For CYP1A, in the in vivo experiments, EF exhibited potent inhibition on the CYP1A-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…injection of 3 mg kg À1 of EF or multi-doses of 1 mg kg À1 were sufficient to cause a generalized depression of CYP activities in sea bass. Enrofloxacin was an effective inactivator of the erythromycin N-demethylase activity (Vaccaro et al 2003;Hu et al 2012), while immunoblot analysis showed a strong decrease in staining intensity of a protein band immunoreactive with anti-CYP3A27. Therefore, it can be postulated that fluoroquinoloneantibiotics such as EF in sea bass have an adverse reaction with the CYP enzymes, and hence a strong potential to cause long-lasting interactions.…”
Section: Interactions With Fluoroquinolonesmentioning
confidence: 97%
See 3 more Smart Citations
“…injection of 3 mg kg À1 of EF or multi-doses of 1 mg kg À1 were sufficient to cause a generalized depression of CYP activities in sea bass. Enrofloxacin was an effective inactivator of the erythromycin N-demethylase activity (Vaccaro et al 2003;Hu et al 2012), while immunoblot analysis showed a strong decrease in staining intensity of a protein band immunoreactive with anti-CYP3A27. Therefore, it can be postulated that fluoroquinoloneantibiotics such as EF in sea bass have an adverse reaction with the CYP enzymes, and hence a strong potential to cause long-lasting interactions.…”
Section: Interactions With Fluoroquinolonesmentioning
confidence: 97%
“…; Hu et al . ), while immunoblot analysis showed a strong decrease in staining intensity of a protein band immunoreactive with anti‐CYP3A27. Therefore, it can be postulated that fluoroquinolone‐antibiotics such as EF in sea bass have an adverse reaction with the CYP enzymes, and hence a strong potential to cause long‐lasting interactions.…”
Section: Interactions With Fluoroquinolonesmentioning
confidence: 97%
See 2 more Smart Citations
“…Crucian carp is an omnivorous freshwater fish native to China. Aquaculture of this fish in China has expanded rapidly because of its fast growth, use of natural foods, tender flesh, and high resistance to disease (Hu et al 2012). However, very few reports are available concerning hepatic lipid metabolism in this fish subjected to trichlorfon exposure.…”
mentioning
confidence: 99%